Projeto de uma máquina de fadiga para avaliação de esforços em componentes de suspensão de veículos do tipo Baja Sae - Lima, Pedro Paulo dos Santos (Universidade Federal Rural do Semi-Árido, 2020)
Most of the failures in mechanical components are due to alternative efforts, in other words, loads that vary continuously over time. Although presenting significantly lower stress levels when compared to the maximum supported by the component, in large cycles these efforts can result in failure due to fatigue. This phenomenon is greatly intensified in dynamic applications, since the components are not subjected only to point stresses or loads, but to multiaxial stresses depending on their kinetic (ABRAHÃO et al, 2008). Baja SAE vehicles are aimed at students from engineering universities in Brazil and the world. They design, model, manufacture and subsequently test and validate their projects in the most diverse ways possible. As this vehicle is intended for the off-road segment, very rigorous tests are required, especially with regard to the problem of resistance to overcoming obstacles (BAJA SAE Brasil, 2019). Observing as a problem mentioned above that this search work develops methods of fatigue analysis in suspension components of these vehicles, such as the referred car system, probably, or the most submitted in the Baja SAE competitions. For this reason, the aim is to develop a whole methodology and design management for formulating and obtaining a prototype of a fatigue testing machine, aided by an embedded electronics system for monitoring and evaluating the results obtained.
Keywords: Gerenciamento de projeto; Fadiga; Máquina para teste de fadiga; Design management; Fatigue; Fatigue testing machine; ENGENHARIAS::ENGENHARIA MECANICA